2019
DOI: 10.3390/cells8080909
|View full text |Cite
|
Sign up to set email alerts
|

Rab GTPases: Switching to Human Diseases

Abstract: Rab proteins compose the largest family of small GTPases and control the different steps of intracellular membrane traffic. More recently, they have been shown to also regulate cell signaling, division, survival, and migration. The regulation of these processes generally occurs through recruitment of effectors and regulatory proteins, which control the association of Rab proteins to membranes and their activation state. Alterations in Rab proteins and their effectors are associated with multiple human diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 224 publications
(296 reference statements)
0
59
0
3
Order By: Relevance
“…Dysregulated Rab5 activity has been defined as a major pathogenic driver in AD [1,48,70]. Moreover, a pathogenic role of aberrant Rab5 is emerging in many of the same other neurodegenerative diseases that are being targeted by p38α inhibitor programs, including PD, DLB, ALS, and HD [71][72][73]. Rab5 is a member of a large family of Rab proteins involved with neuronal function [53,71] and a number of other Rab proteins have been connected to neurodegenerative disease.…”
Section: Role Of Dysregulated Rab5 In the Pathogenesis Of Neurodegenementioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated Rab5 activity has been defined as a major pathogenic driver in AD [1,48,70]. Moreover, a pathogenic role of aberrant Rab5 is emerging in many of the same other neurodegenerative diseases that are being targeted by p38α inhibitor programs, including PD, DLB, ALS, and HD [71][72][73]. Rab5 is a member of a large family of Rab proteins involved with neuronal function [53,71] and a number of other Rab proteins have been connected to neurodegenerative disease.…”
Section: Role Of Dysregulated Rab5 In the Pathogenesis Of Neurodegenementioning
confidence: 99%
“…However, as will be discussed in Section 5, Rab5 activity has been robustly connected to p38 MAPK signaling, while no such connection has been established for the other Rab proteins. Therefore, this review is focused on Rab5, and the reader is referred to a number of other excellent recent reviews on the broader family of Rab proteins and their relation to the pathogenesis of neurodegenerative disease [71][72][73].…”
Section: Role Of Dysregulated Rab5 In the Pathogenesis Of Neurodegenementioning
confidence: 99%
“…Several previous studies provide experimental evidence to support a link between endosomal defects and neuronal pathology in NDs, which has been well-reviewed in recent articles (Kiral et al, 2018;Guadagno and Progida, 2019). For example, in postmortem brains of AD patients, enlargement of Rab5-positive EEs and upregulation of Rab4 were observed in pyramidal neurons of the prefrontal cortex at the early-stages (Cataldo et al, 2000), and upregulation of Rab4, Rab5, Rab7, and Rab27 was observed in the cholinergic basal forebrain neurons (Ginsberg et al, 2011).…”
Section: Evidence For the Involvement Of Local Rab-mediated Endocyticmentioning
confidence: 92%
“…Rab proteins have been one of the families of the Ras superfamily mostly studied (Guadagno and Progida, 2019). However, their role in tumor progression emerged more recently.…”
Section: Rab Family Proteins and Their Role In Melanoma Metastasis Anmentioning
confidence: 99%